Temperature Sensing in Cells Using Polymeric Upconversion Nanocapsules - Iyisan, Banu (Biomacromolecules, 2020)
[Image: see text] Monitoring local temperature inside cells is crucial when interpreting biological activities as enhanced cellular metabolism leads to higher heat production and is commonly correlated with the presence of diseases such as cancer. In this study, we report on polymeric upconversion nanocapsules for potential use as local nanothermometers in cells by exploiting the temperature dependence of the triplet–triplet annihilation upconversion phenomenon. Nanocapsules synthesized by the miniemulsion solvent evaporation technique are composed of a polymer shell and a liquid core of rice bran oil, hosting triplet–triplet annihilation upconversion active dyes as sensitizer and emitter molecules. The sensitivity of the triplet–triplet annihilation upconversion to the local oxygen concentration was overcome by the oxygen reduction ability of the rice bran oil core. The triplet–triplet annihilation upconversion process could thus successfully be applied at different levels of oxygen presence including at ambient conditions. Using this method, the local temperature within a range of 22 to 40 °C could be determined when the upconversion nanocapsules were taken up by HeLa cells with good cellular viability. Thus, the higher cell temperatures where the cells show enhanced metabolic activity led to a significant increase in the delayed fluorescence spectrum of the upconversion nanocapsules. These findings are promising for further development of novel treatment and diagnostic tools in medicine.